AB1221 POPULATION WIDE STUDY OF MORTALITY IN ANCA-ASSOCIATED VASCULITIS IN WESTERN AUSTRALIA FROM 2000 TO 2014. (13th June 2020) - Taylor, W.; Raymond, W.; Keen, H.; Inderjeeth, C.; Preen, D.; ". Nossent, J.
Abstract : Background: Survival in ANCA-associated vasculitis (AAV) has improved substantially in the last fifty years, but Australian data and studies with a control population are scarce. Objectives: The aim of this study was to compare the all-cause mortality rate between patients with AAV and matched controls in Western Australia. Methods: A retrospective population-based cohort study conducted using the Western Australia Health Data Linkage System (WADLS) for patients with a diagnostic code for AAV (International Classification of Diseases (ICD)-10-AM M30.1, M31.3 and M31.7). We included 240 patients with AAV (mean age 57.37 ± 16.69, 48.8% males) who had a hospital admission or emergency department visit between 1 January 2000 and 31 December 2014 and 4406 controls matched for age and sex. Death details were obtained from the WA Death registry. Mortality rates per 1000 person-years (MR) for AAV patients and controls were compared by mortality rate ratios (MRRs) with 95% CI. Kaplan Meijer survival estimates were analyzed by log-rank test. Results: During a mean follow-up of 6.58 years (3.37, 11.25) 83 incident AAV patients (34.6%) died, giving a mortality rate of 48.13 per 1000 person-years (95% CI 38.33, 59.66). This was 82% higher overall than in controls (MRR 1.82, 95% CI 1.46, 2.26, P < 0.0001), while the MRR for males with AAV was 2.28 (95% CI 1.46, 2.26; P < 0.0001) and for females 1.43 (95% CI 1.01, 2.02; P = 0.0267). Survival estimates at one (90.5%) and five years (75%) were significantly lower in AAV patients than controls. Conclusion: Over the last fifteen years, the mortality risk for AAV patients remains significantly increased compared with matched controls and more so for male than female AAV patients. Together with the reduced one- and five-year survival rate, this indicates the need for further improvements in initial disease management in order to reduce the risk of death in AAV. Acknowledgments: The authors thank the Data Custodians of the Hospital Morbidity Data Collection (HMDC), Emergency Department Data Collection (EDDC), the State Registry of Births, Deaths and Marriages, the WA Electoral Commission, and the staff at Data Linkage Branch at the Western Australian Department of Health for their assistance in provision of data. This work was supported by an unrestricted grant from the Arthritis Foundation of Western Australia. Author WDR received a PhD Scholarship in Memory of John Donald Stewart from the Arthritis Foundation of Western Australia Disclosure of Interests: Wade Taylor: None declared, warren raymond: None declared, Helen Keen Speakers bureau: Pfizer Austrlaia, Abbvie Australia, Charles Inderjeeth Consultant of: Linear Research Perth, David Preen: None declared, Johannes ("Hans") Nossent Speakers bureau: Janssen